2013
DOI: 10.1088/1612-2011/10/3/035001
|View full text |Cite
|
Sign up to set email alerts
|

Single-frequency Q-switched double-pulse Nd:YAG laser

Abstract: A laser diode dual-end-pumped injection-seeded single-frequency Q-switched double-pulse Nd:YAG laser is designed using a modified ramp-fire technique. The laser is capable of producing a pair of Q-switched single-frequency 1064 nm laser pulses in one pump period. Every pulse has an output energy of up to 10 mJ, width of nearly 20 ns, and interval of about 200 μs between two Q-switched pulses. The optical-to-optical efficiency of this laser is about 22.4% and its slope efficiency is 28%. A narrow spectrum linew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The entire generation and pre-pumping process therefore takes such a long time that it can be repeated only after a period of several hundred microseconds. In contrast, a single pumping operation usually results in the generation of a single short, strong pulse, and the generation of the next one requires the cycle to be repeated or the pumping time to be significantly extended [1].…”
Section: Introductionmentioning
confidence: 99%
“…The entire generation and pre-pumping process therefore takes such a long time that it can be repeated only after a period of several hundred microseconds. In contrast, a single pumping operation usually results in the generation of a single short, strong pulse, and the generation of the next one requires the cycle to be repeated or the pumping time to be significantly extended [1].…”
Section: Introductionmentioning
confidence: 99%
“…The pulse energy of 100 mJ was obtained at the repetition rate of 10 Hz, and the pulse width was approximately 8 ns. In 2013, Li et al reported that in an injection-seeded Q-switched Nd:YAG laser, stable single-longitudinal-mode (SLM) emission with double-pulse output was successfully obtained [5,6]. A hybrid MOPA system, which consists of a seeder laser, an acousto-optic modulator (AOM), fiber amplifiers and bulk amplifiers, is a compact and most effective design to obtain high pulse energy and high beam quality laser output.…”
Section: Introductionmentioning
confidence: 99%
“…Several different solid-state laser host materials [2][3][4][5] are capable of delivering efficient laser action of which YLiF4 (YLF) has some unsurpassed characteristics that are vital to many applications. In particular, the weak thermal lensing, natural birefringence, and long upper-laser-level lifetime are important for good beam quality and many applications such as Q-switching [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%